Pengaruh Material Bangunan Terhadap Kenyamanan Pengguna Dalam Cerpen In Coeli Quies Karya Lidwina Ika - Hanifah Dian Pertiwi; Salmannisa Yumna Nur Safitri; Eva Dwi Kurniawan (BADAN PENERBIT STIEPARI PRESS, 2024)
A short story or short story is a literary work that tells the main character of an event and is packaged into a dense story. In the short story entitled